A Questionnaire-Based Survey to Assess the Level of Knowledge and Awareness about Drug-Food Interactions among General Public in Western Saudi Arabia - Syed Faisal Zaidi; Rayan Mgarry; Abdullah Alsanea; Sakar Khalid Almutairi; Yaser Alsinnari; Saad Alsobaei; Kanwal Ahmed (MDPI AG, 2021)
Introduction: Various drug-food interactions exist that may hinder treatment and can sometimes be lethal. Our aim was to assess the level of public knowledge and awareness in Jeddah city, Western Saudi Arabia, about drug-food interactions, along with the effects of demographics on their knowledge. Methods: A survey questionnaire was administered in this cross-sectional study to participants spread across multiple locations in Jeddah, including in malls and public gatherings. Participants included both males and females. Sample size was calculated through Raosoft® software. Data analysis was executed using IBM Statistic SPSS and the level of statistical significance was set at p < 0.05. Results: A total of 410 people participated in the study and only 92.68% (380) of responses were enrolled in the study; 7.32% (30) were not enrolled due to the exclusion criteria. Surprisingly, only six out of eighteen questions regarding drug-food interactions in the administered questionnaire were correctly answered by 380 participants. Data indicated that the participants had a poor to intermediate level of both knowledge and awareness with respect to drug-food interactions. Furthermore, participants showed moderate to strong awareness of the effects of alcohol and tea generally, and their interaction with medication. Conclusion: Participants in our study showed inadequate knowledge of basic and fundamental information about drug-food interactions, which highlights the dire need to increase awareness.